QUALITY IMPROVEMENTS IN THE PACKAGING OF MSR RICE PRODUCT USING SIX SIGMA METHOD AND FUZZY ANALYTICAL HIERARCHY PROCESS - Lohanatha, Anastacia; Fitriana, Rina; Febriani, Elfira (Department of Agroindustrial Technology, Bogor Agricultural University, 2024)
The company has problems in production, one of which is that there is defective packaging on the product. The product that became the object of research was Packaging of Product MSR, which was most often returned from distributors because it did not comply with the specified quality with an average percentage of 1.08%. This study aims to identify the factors that cause defects in MSR products and provide suggestions for improvements to minimize defects and improve the quality of the production process. Quality improvement is carried out using the Six Sigma method with the stages of Define, Measure, Analyze, Improve, and Control and the Fuzzy Analytical Hierarchy Process. the DPMO value obtained was 8211.43 with a sigma level of 3.899. In the Failure Mode Effect Analysis calculation, the four highest causes were found namely packaging that did not meet the requirements, the sealer machine was too hot, rice buildup during storage and the printing machine was damaged. The best alternative is determined using the Fuzzy Analytical Hierarchy Process with the criteria of cost, materials, maintenance and storage. The selected improvement proposals are the creation of a form for routine inspection, cleaning of packaging machines and creating an alarm for every 730 products, and manufacturing of shelves for product storage. Keywords: define measure analyze improve control, fuzzy analytical hierarchy process, failure mode effect analysis, six sigma